Development of Architecture and Structural Diagram of Regional Optical-Fiber Communication Lines (Eurasian Journal of Learning and Academic Teaching, 2023)
The article discusses the advantages, scope, block diagrams of fiber optic communication lines of regional telecommunication communication networks, also talks about the capabilities of fiber optic communication lines and the high quality of information transmission over fiber optic communication lines and talks about the information security of fiber optic communication lines